Effect of a Rapid Tooling Technique in a 3D Printed Part for Developing an EDM Electrode - Turki Alamro; Mohammed Yunus; Rami Alfattani; Ibrahim A. Alnaser (International Journal of Polymer Science)
The role of rapid tooling (RT) in additive manufacturing (AM) seems essential in improving and spreading out the vista of manufacturing proficiency. In this article, attempts were made to discover the feasibility and the accomplishments of the RT electrode in the field of electro-discharge machining (EDM). Fused deposition modeling (FDM) is one of the AM processes adopted to fabricate the EDM electrode prototype by coating with copper. The copper is deposited on FDM-built ABS plastic component for about 1 mm through thick electroplating. The copper-coated FDM (CCF) and solid copper (SC) electrodes are used to conduct experiments on a die-sinking EDM machine using tool alloy steel as a workpiece. The CCF polymer electrode can be efficiently used in EDM operations as the build time of any complex shape was substantially reduced. However, the material removal rate (MRR) is far less than that of the SC electrode. It is recommended that the CCF electrode is used for semifinishing and finishing operations in which MRR happens to be less. However, CCF can get spoiled as high temperatures are generated on the machining tool, and the plastic core hardly sustains such high temperatures.